The economic results of farms in the Czech Republic - Jaroslav Svoboda; Martina Novotn (Journal of Central European Agriculture, 2014)
Czech agrarian sector has undergone significant changes during last ten years. Since the Czech Republic has entered the European Union in 2004, agrarian sector has had to adapt to conditions of the Common Agricultural Policy (CAP). This policy is taken as a crucial within the EU policies as it includes orientation of food production as well as a broader sense of sustainable development and employment. The paper assesses profit/loss and its efficiency of a sample of farms in the Czech Republic (about 830 farms) in 2004 2010. This analysis employed methods of financial analysis both traditional ratios and systems of bankruptcy and value models). Time series is long enough to monitor results after establishing the UE and the CAP principles in the Czech Republic. The paper shows that although since 2004, revenue per employee has been increasing, the value added per worker has been static without any major changes. However, farms on average were profitable with the exception of 2009. It was verified by bankruptcy and value models that an average farm is in a relatively good financial situation (without any problems or debt and sufficiently liquid).